2020
DOI: 10.1182/bloodadvances.2019001411
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency predicts for poor overall survival in white but not African American patients with multiple myeloma

Abstract: Key Points Vitamin D deficiency is a predictor for poor overall survival in patients with multiple myeloma, even after adjusting for age and stage. This difference is only observed in white patients, not African Americans, even under a lower threshold for deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…The literature search through PubMed, EMBASE, Cochrane Library databases, and three conference proceedings (ASH, ASCO, and EHA) identified 1212 articles after duplicates removed, of which 52 were considered relevant through the evaluation of titles and abstracts. Among them, 30 articles fulfilled the criteria for this meta-analysis: 5 articles on myeloid malignancies [17][18][19][20][21] , 20 on lymphoid malignancies 18,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] , 3 on autologous HSCT (ASCT) [41][42][43] , and 3 on allo-HSCT [44][45][46] . A flow diagram of the article selection process is shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search through PubMed, EMBASE, Cochrane Library databases, and three conference proceedings (ASH, ASCO, and EHA) identified 1212 articles after duplicates removed, of which 52 were considered relevant through the evaluation of titles and abstracts. Among them, 30 articles fulfilled the criteria for this meta-analysis: 5 articles on myeloid malignancies [17][18][19][20][21] , 20 on lymphoid malignancies 18,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] , 3 on autologous HSCT (ASCT) [41][42][43] , and 3 on allo-HSCT [44][45][46] . A flow diagram of the article selection process is shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Seventh, for multiple myeloma (MM), only one article was included in our search 35 , which reported that lower vitamin D status was significantly associated with poor OS (HR: 1.34, p = 0.008). They showed that its impact on OS was only observed in Caucasian patients (HR: 1.45, p = 0.005), but not in African Americans, suggesting a difference between ethnic groups.…”
Section: Vitamin D Level In Multiple Myeloma At Diagnosismentioning
confidence: 99%
“…Therefore, we aimed to test the hypothesis that serum 25(OH)D concentration is associated with mental health and life stress measurements including depression, trait anxiety, perceived stress, and hostility in young adults. Moreover, previous studies have found a race difference in the effects of vitamin D on health outcomes [ 25 , 26 ], and sex hormones are closely related to vitamin D status [ 27 ]. Therefore, we also aimed to investigate gender and race disparities in these associations.…”
Section: Introductionmentioning
confidence: 99%
“…In a neoplastic subset of patients, most of whom suffered symptomatic multiple myeloma (MM), VitD deficiency was frequently related to a late stage of the disease, reduced survival, and greater risk of the progression and development of pathological fractures in asymptomatic patients [ 26 ]. Pleiomorphisms of the VDR often participate in the development of deficiency states [ 27 ], which can be overcome by supplementation with VitD or analogues. In addition, VitD has been found to improve osteoblastic differentiation and maturation, which also reduces the lineage switching of MM plasma cells through an osteoclast-like transformation.…”
Section: Introductionmentioning
confidence: 99%